Perceptions of adolescents from the Sterkspruit area, Eastern Cape Province, South Africa, regarding the underlying factors that have an impact on their right to adequate food - Rosseau, Carla Yvonne (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.